The Prokaryotes Prokaryotic Communities and Ecophysiology - Rosenberg, Eugene; DeLong, Edward F.; Lory, Stephen; Stackebrandt, Erko.; Thompson, Fabiano; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
The Prokaryotes is a comprehensive, multi-authored, peer reviewed reference work on Bacteria and Achaea. This fourth edition of The Prokaryotes is organized to cover all taxonomic diversity, using the family level to delineate chapters. Different from other resources, this new Springer product includes not only taxonomy, but also prokaryotic biology and technology of taxa in a broad context. Technological aspects highlight the usefulness of prokaryotes in processes and products, including biocontrol agents and as genetics tools. The content of the expanded fourth edition is divided into two parts: Part 1 contains review chapters dealing with the most important general concepts in molecular, applied and general prokaryote biology; Part 2 describes the known properties of specific taxonomic groups. Two completely new sections have been added to Part 1: bacterial communities and human bacteriology. The bacterial communities section reflects the growing realization that studies on pure cultures of bacteria have led to an incomplete picture of the microbial world for two fundamental reasons: the vast majority of bacteria in soil, water and associated with biological tissues are currently not culturable, and that an understanding of microbial ecology requires knowledge on how different bacterial species interact with each other in their natural environment. The new section on human microbiology deals with bacteria associated with healthy humans and bacterial pathogenesis. Each of the major human diseases caused by bacteria is reviewed, from identifying the pathogens by classical clinical and non-culturing techniques to the biochemical mechanisms of the disease process. The 4th edition of The Prokaryotes is the most complete resource on the biology of prokaryotes.
Preface -- Foreword.-About the Editors -- List of Contributors -- (Section 1) Prokaryotic Communities -- The Structure and Function of Microbial Communities -- Overview: Quantitative and Theoretical Microbial Population Biology -- Structure and Function of Prokaryotic Communities in Soils of Polar and High-Elevation Deserts -- Plant Rhizosphere Microbial Communities -- Tropical Soil Bacterial Communities -- Freshwater Microbial Communities -- Pelagic Prokaryotic Communities Inhabiting Marine Oxygen Minimum Zones -- Marine Deep Sediment Microbial Communities -- Sea-Ice Microbiology -- Coral Reef Microbial Communities -- (Section 2) Ecophysiology: Planktonic Versus Sessile Life of Prokaryotes -- The Phototrophic Way of Life -- The Anaerobic Way of Life -- The Chemolithotrophic Prokaryotes -- Bacterial Swimming Behavior -- Prokaryotic Life Cycles -- Life at High Temperatures -- Life at Low Temperatures -- Life at High Salt Concentrations -- Prokaryotic Alkaliphiles -- Syntrophism Among Prokaryotes -- Quorum Sensing -- Cell-Cell Interactions in Swarming and in Fruiting Body Development.
Keywords: Life sciences; Microbiology; Life Sciences; Microbiology